PENGGUNAAN MEDIA PEMBELAJARAN SEMPOA UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA KELAS II MI MA’ARIF NU 9 PURBOLINGGO - Atika Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low Mathematics learning outcomes of second- grade students of MI Ma'arif NU 9 Purbolinggo. In the pre-cycle stage, only 2 out of 23 students or 8.7% achieved learning mastery. Therefore, the implementation of more effective and interesting learning media is needed to improve student learning outcomes. This study aims to improve Mathematics learning outcomes through the use of abacus learning media. The research method used is Classroom Action Research (CAR) which is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The research instruments include learning outcome tests, teacher activity observation sheets, and student activity observation sheets. The results of the study showed an increase in student learning outcomes, where in cycle I the learning completeness increased to 13 students (56.5%), and in cycle II it increased to 20 students (87%). Thus, there was an increase of 78.3% from pre- cycle to cycle II, and an increase of 30.5% from cycle I to cycle II. Based on the observation results, it can be concluded that the use of abacus media is effective in improving students' understanding of number concepts and Mathematics learning outcomes. In addition, this media is able to create more interesting and interactive learning so that it can be used as an alternative Mathematics learning strategy in elementary schools.